Myringoplasty graft uptake: Short and long term outcome - Acharya, Roshan; Tulachan, Bishow; Acharya, Anup (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Myringoplasty is surgical procedure to restore tympanic membrane perforation. The objective of the study is to compare overall success rate of myringoplasty after 6 weeks and 6 months post-operatively. MATERIAL AND METHODS This is a retrospective, comparative study carried out in the Department of ENT (Ear, Nose and Throat) and Head and Neck Surgery (ENT-HNS), Universal College of Medical Sciences-Teaching Hospital (UCMS-TH), Bhairahawa, Rupandehi, Nepal. All the data was collected from the operative notes and operative record book of our hospital which were done from October 2018 to September 2020 over a period of 24 months by single surgeon. A total of 77 patients with age range of 12-70 years including all gender with chronic otitis media (COM) mucosal type, inactive who underwent myringoplasty were studied. Graft uptake results were assessed after 6 weeks and 6 months following surgery. RESULTS The age of the patients ranged from 12-70 years. The mean ± standard deviation (S.D) of age was 27.84 ± 13.16 years. There were 47 (61%) female patients and 30 (39%) male patients involved in the study. Graft uptake success rates were 84.4% (65) and 83.1% (64) after 6 weeks and 6 months respectively. CONCLUSION No statistical significance was noted in graft success and failure rates between 6 weeks and 6 months (p = 0.320).